2012
DOI: 10.1088/1742-6596/388/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Resonant enhanced electron impact dissociation of molecules

Abstract: Abstract. In the collision of electrons with molecules and molecular ions, excitation and dissociation are dominated by resonant processes, where the electron becomes temporarily trapped, changing the forces felt by the nuclei. We have carried out calculations on the resonant process leading to dissociative attachment and dissociative recombination. We separate the problem into two steps. First, the resonance parameters are obtained from accurate electron scattering calculations using the Complex Kohn variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A recent study by Slaughter et al (2012) identified the signature of a shape resonance of 3 u symmetry among the many Feshbach resonances in their electron -O + 2 collision calculations. We therefore undertook a search for similar structures in molecular nitrogen.…”
Section: Potential Energy Curves Quantum Defects and Shape Resonancesmentioning
confidence: 99%
“…A recent study by Slaughter et al (2012) identified the signature of a shape resonance of 3 u symmetry among the many Feshbach resonances in their electron -O + 2 collision calculations. We therefore undertook a search for similar structures in molecular nitrogen.…”
Section: Potential Energy Curves Quantum Defects and Shape Resonancesmentioning
confidence: 99%
“…Other CPESs were calculated in a fashion similar to the strategy employed in ref , in which the two components, real and imaginary, of the CPES are calculated by two separate techniques. For example in refs the real part was approximated via a configuration-interaction calculation, while the imaginary part (the width) was extracted from complex Kohn scattering calculations. Another example is the Fano-ADC-Stieltjes approach, in which the real part is calculated by algebraic diagrammatic construction scheme up to second order [ADC(2)] and the decay rates by using the Fano theory of resonances. , Alternatively, CPESs were also calculated by CAPs within ADC(2) (where the two complex parts were treated concurrently). , With everything considered, ab initio CPES are not abundant.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the kinetic energy distribution measurements were calibrated using the kinetic energy of the oxygen anions from O 2 at the same resonance energy [23]. Additionally, both calibrations were confirmed by measuring the O − ion kinetic energy from DEA to CO 2 at 8.2 eV [24].…”
Section: Experimental and Computational Methodologymentioning
confidence: 93%